The Influence of Return on Assets (RoA), Return on Equity (RoE), and Leverage, and Company Size on Tax Avoidance in Banks Listed on the Indonesian Stock Exchange in 2018-2021 - Yenni Aurelia Lysander; Jholant Bringg Luck Amelia Br Sinaga; Carolina Gulo; Wilfreda Tania; Dearma Sariani Sinaga (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
This research was conducted to determine the influence of Return On Assets, Return On Equity, Leverage, and Company Size on Tax Avoidance listed on the Indonesia Stock Exchange in 2018-2021. The sample used in this research is banking companies listed on the Indonesia Stock Exchange. The sampling technique was purposive, determined using criteria, and obtained 84 samples. The testing in this research uses the multiple linear regression method to see the effect of Return On Assets, Return On Equity, Leverage, and Company Size using supporting software, namely SPSS. The research results show that Return On Assets has no effect on Tax Avoidance, Return On Equity has an effect on Tax Avoidance.